Active site directed chemical modification of alpha-galactosidase from bacillus stearothermophilus (NCIM 5146): involvement of lysine, tryptophan and carboxylate residues in catalytic site - Gote, M. M.; Khan, Mohammad Islam; Khire, Jayant Malhar (Enzyme and Microbial Technology, 2007)
The catalytic amino acid residues of the extracellular a-galactosidase (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) from Bacillus stearothermophilus NCIM 5146 were investigated by pH dependence and chemical modification studies. These results suggested that carboxylate and a lysine residue take part in catalysis and only lysine residues were essential for substrate binding. Carbodiimide mediated chemical modification of the enzyme also supported that a carboxylate residue located in the active site act as a nucleophile base in substrate cleavage. Acylation and reductive methylation of lysine residues by acetic, citraconic anhydride and sodium borohydride suggested that four protonated lysine residues carrying positive charge on its epsilon-amino group provides the positive charge density for binding of the substrate. Additionally four tryptophan residues also found near to the active site and in a moderately hydrophobic environment. Kinetic and thermal inactivation study of modified enzyme indicated that these tryptophan residues might have a role in the catalytic site as well as in the thermal stabilization of active site conformation at higher temperature. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Active site; alpha-galactosidase; Bacillus stearothermophilus; carboxylate; Chemical modification; lysine; Tryptophan

Fluorescence resonance energy transfer from tryptophan to folic acid in micellar media and deionised water - Mote, U. S.; Patil, S. R.; Bhosale, Siddharth H.; Han, Sung-Hwan; Kolekar, G. B. (Journal of Photochemistry and Photobiology B-Biology, 2011)
The fluorescence resonance energy transfer (FRET) from tryptophan (Trp) to folic acid (FA) in aqueous sodiumdodecyl sulphate, cetyltrimethyl ammonium bromide, and Brij-35 as well as deionised water was investigated using steady state and time resolved fluorescence techniques. The data obtained from steady state fluorescence spectral studies and time resolved measurement indicated that the FRET from Trp to FA occurred most effectively in aqueous sodium dodecyl sulphate micellar solutions. The distance between Trp and FA were evaluated. Binding constant, number of binding sites and thermodynamic parameters were determined for Trp-FA interactions in deionised water. The values of the thermodynamic parameters suggest that the hydrophobic forces and hydrogen bonding are the key interacting forces between Trp-FA interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quenching; Fluorescence resonance energy transfer (FRET); Folic acid; Foster theory; Stern-Volmer plot; Tryptophan

Tryptophan environment and functional characterization of a kinetically stable serine protease containing a polyproline II fold - Rohamare, Sonali B.; Gaikwad, Sushama M. (Journal of Fluorescence, 2014)
The single tryptophan residue from Nocardiopsis sp. serine protease (NprotI) was studied for its microenvironment using steady state and time-resolved fluorescence. The emission maximum was observed at 353 nm with excitation at 295 nm indicating tryptophan to be solvent exposed. Upon denaturation with 6 M guanidinum thiocyanate (GuSCN) the emission maxima was shifted to 360 nm. Solute quenching studies were performed with neutral (acrylamide) and ionic (I- and Cs+) quenchers to probe the exposure and accessibility of tryptophan residue of the protein. Maximum quenching was observed with acrylamide. In the native state, quenching was not observed with Cs+ indicating presence of only positively charged environment surrounding tryptophan. However; in denatured protein, quenching was observed with Cs+, indicating charge reorientation after denaturation. No quenching was observed with Cs+ even at pH 1.0 or 10.0; while at acidic pH, a higher rate of quenching was observed with KI. This indicated presence of more positive charge surrounding tryptophan at acidic pH. In time resolved fluorescence measurements, the fluorescence decay curves could be best fitted to monoexponential pattern with lifetimes of 5.13 ns for NprotI indicating one conformer of the trp. Chemical modification studies with phenyl glyoxal suggested presence of Arg near the active site of the enzyme. No inhibition was seen with soyabean trypsin and limabean inhibitors, while, CanPI uncompetitively inhibited NprotI. Various salts from Hofmeister series were shown to decrease the activity and PPII content of NprotI.
Keywords: Fluorescence quenching; Hofmeister series; Nocardiopsis; Serine protease; Tryptophan

Novel pentadecyl phenol-tagged L-tryptophan molecules: synthesis, self- assembly and liquid crystalline properties - Parappurath, Akhil; Abraham, Jancy Nixon (Chemistryselect, 2018)
The paper describes the self-assembly and liquid crystalline properties of pentadecylphenol tagged L-tryptophan molecules having ester and amide functionality. We have synthesized a series of molecules having mono and ditryptophan moieties attached to pentadecylphenol through amide or ester linkage. The fluorescence properties of the Boc-L-tryptophan-pentadecylphenol molecules were measured in methanol and found to aggregate beyond the critical aggregation concentration and self-assembled to give spherical structures. Upon deprotection of Boc group, the amine end group got involved in extended hydrogen bonding and fibril like structures were developed. These molecules also showed liquid crystalline behavior in hydrogen bonding solvents such as benzyl alcohol and showed needle like crystals in tert-butanol, as analyzed by polarized optical light microscopy.
Keywords: Cardanol; liquid crystalline; pentadecylphenol; Self-assembly; Tryptophan

Tryptophan-cardanol fluorescent nanoparticles inhibit alpha-synuclein aggregation and disrupt amyloid fibrils - Sunny, Lisni P.; Srikanth, Priya; Sunitha, Anju Kunhiraman; Tembulkar, Niyoti; Abraham, Jancy Nixon (Journal of Peptide Science, 2022)
Protein misfolding and aggregation play a vital role in several human diseases such as Parkinson's, Alzheimer's, and prion diseases. The development of nanoparticles that modulate aggregation could be potential drug candidates for these neurodegenerative disorders. Parkinson's disease pathogenesis is closely associated with the accumulation of alpha-synuclein oligomers and fibrils in the substantia nigra of the brain. This report discusses the interactions of novel tryptophan-cardanol nanoparticles with alpha-synuclein protein monomers and fibrils. These nanoparticles could effectively disrupt alpha-synuclein fibrils and inhibit fibril formation at low concentrations such as 5 mu M. The tryptophan-cardanol nanoparticles inhibit fibril formation from unstructured protein resulting in spherical nanostructures. These nanoparticles could also disassemble amyloid fibrils; the complete disappearance of fibrils was evident after 48 h of incubation with tryptophan-cardanol. The transmission electron microscopy (TEM) micrographs after the incubation did not show any remnants of the peptide aggregates or oligomers. The thioflavin T fluorescence after the disassembly was diminished compared with that of fibrils also supports the inhibitory effect of the nanoparticles. Also, these nanoparticles did not reduce the viability of the SH-SY5Y cells. These findings suggest that the tryptophan-cardanol nanoparticles showed sufficiently high inhibitory activity and may have therapeutic potential for synucleinopathies.
Keywords: alpha-synuclein; amyloid fibrils; Cardanol; inhibitors; Tryptophan